A full-solid-state battery cell with a three-dimensional interlaced lithium ion conduction network and its preparation method and application
By building a three-dimensional interlaced lithium-ion conduction network in an all-solid-state lithium-ion battery, the problems of low lithium-ion conductivity and large interface impedance are solved, and higher battery performance and longer cycle life are achieved.
Patent Information
- Application Number
- CN202510012480.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-06
AI Technical Summary
All-solid-state lithium-ion batteries face interfacial impedance problems caused by low lithium ion conductivity, poor interface contact and prone to cracks during charge and discharge cycles.
By introducing low-viscosity thermoplastics and electrostatic dry spraying technology, a three-dimensional interlaced lithium ion conduction network is constructed to form a layered powder cell, including composite positive electrode, sulfide electrolyte and composite negative electrode powder, and an all-solid-state battery cell is prepared through electrostatic spraying and integrated compression.
Significantly improve the efficiency of lithium ion migration, enhance the interface stability between the electrode and the solid electrolyte, reduce the interface impedance, and achieve better capacity retention, longer cycle life and better safety performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid-state batteries, and specifically relates to an all-solid-state battery cell with a three-dimensional interlaced lithium ion conduction network, and a preparation method and application thereof. Background Art
[0002] All-solid-state sulfide solid-state batteries have significant safety advantages over traditional liquid electrolyte lithium-ion batteries because they are non-flammable and can operate stably over a wider temperature range; at the same time, due to the use of high ionic conductivity sulfide electrolytes, such batteries are expected to achieve higher energy density, support longer cycle life, and can use metallic lithium as the negative electrode material, thereby greatly improving the overall performance of the battery. The main challenges facing current all-solid-state battery technology include low lithium ion conductivity, poor interface contact, and interface impedance problems caused by cracks that are prone to occur during charge and discharge cycles.
[0003] Although solid-state electrolytes have brought significant safety improvements, they still face a major technical bottleneck in practical applications - the interface impedance problem. This problem is mainly reflected in the following aspects: 1. Large initial interface impedance: Since the positive electrode, solid electrolyte, and negative electrode are all solid materials, the direct contact between them is not as easy as liquid electrolytes to form a good conductive path, resulting in a higher initial interface impedance. 2. Poor interface bonding performance: The contact surface between solid materials is often not as smooth as that of liquid electrolytes, so it is difficult to ensure that the ideal bonding state between the layers of materials is achieved during the battery manufacturing process. 3. Interface changes during charging and discharging: During the charging and discharging process of the battery, the positive and negative electrode materials will undergo volume changes (expansion or contraction), which will cause the already less than ideal interface bonding to further deteriorate, thereby increasing the interface impedance.
[0004] The present invention proposes a new battery structure design, which constructs a three-dimensional staggered lithium ion conduction network by introducing low-viscosity thermoplastic agent and electrostatic dry spraying technology, significantly improving the lithium ion migration efficiency, while enhancing the interface stability between the electrode and the solid electrolyte, thereby reducing the interface impedance of the sulfide solid-state battery to achieve better capacity retention, longer cycle life and better safety performance. Summary of the invention
[0005] The purpose of the present invention is to provide a three-dimensional interlaced lithium ion conductive network of all-solid-state battery cells and its preparation method and application in view of the problems existing in the prior art. The present invention constructs a three-dimensional interlaced lithium ion conductive network by introducing a low-viscosity thermoplastic agent (TPA, etc.) and electrostatic dry spraying technology. Specifically, the positive electrode, sulfide electrolyte, and negative electrode powder are electrostatically sprayed and integrated pressed according to different particle sizes and combination ratios to obtain a three-dimensional interlaced lithium ion conductive network of all-solid-state sulfide battery cells, which are further assembled to obtain an all-solid-state sulfide battery.
[0006] The purpose of the present invention can be achieved by the following scheme:
[0007] The present invention provides an all-solid-state battery cell with a three-dimensional staggered lithium ion conductive network, wherein the all-solid-state battery cell is a pressed layered powder cell; the layered powder cell comprises an electrolyte powder layer, and a positive electrode powder layer and a negative electrode powder layer respectively arranged on both sides of the electrolyte powder layer;
[0008] The positive electrode powder layer includes a composite positive electrode powder C layer, a composite positive electrode powder B layer and a composite positive electrode powder A layer which are sequentially arranged on one side of the electrolyte powder layer from the inside to the outside; wherein the particle size of each component in the composite positive electrode powder A is 10 μm ≤ Dmax ≤ 15 μm, the particle size of each component in the composite positive electrode powder B is 5 μm ≤ Dmax ≤ 10 μm, and the particle size of each component in the composite positive electrode powder C is Dmax ≤ 5 μm;
[0009] The negative electrode powder layer includes a composite negative electrode powder D layer and a composite negative electrode powder E layer which are sequentially arranged on the other side of the electrolyte powder layer from the inside to the outside; wherein the particle size of each component in the composite negative electrode powder D is 5 μm ≤ Dmax, and the particle size of each component in the composite negative electrode powder E is 5 μm ≤ Dmax ≤ 10 μm;
[0010] The particle size Dmax of the electrolyte powder is ≤5 μm.
[0011] The structural composition and particle size range of the battery cell in the present invention are shown in the following table:
[0012]
[0013] The present invention forms a three-dimensional staggered lithium ion conductive network by changing the particle size and electrolyte content gradient in the positive electrode powder layer and the negative electrode powder layer, and obtains an all-solid-state battery cell by electrostatic spraying and integrated pressing. The positive electrode powder is composed of three different particle sizes of A, B, and C and corresponding proportions. The negative electrode powder is composed of two different particle sizes of D and E and corresponding proportions. When the layered powder cell is sprayed, electrostatic spraying is performed in the order of composite positive electrode powder A, composite positive electrode powder B, composite positive electrode powder C, electrolyte powder, composite negative electrode powder D, and composite negative electrode powder E, or sprayed in the opposite order. The spraying method is electrostatic spraying. When spraying, it is preferred to spray the positive electrode powder layer first, then spray the electrolyte powder layer, and finally spray the negative electrode powder layer. The pressing method of the layered powder cell is warm isostatic pressing integrated pressing; the temperature of warm isostatic pressing is 120-180 ° C, and the pressure is 100-300 MPa.
[0014] As one embodiment of the present invention, the particle size of the composite positive electrode powder C is preferably 2μm≤Dmax≤5μm, the particle size of the composite negative electrode powder D layer is preferably 2μm≤Dmax≤5μm, and the particle size of the electrolyte powder is preferably 3μm≤Dmax≤5μm.
[0015] As an embodiment of the present invention, the particle size difference between composite positive electrode powder A and composite positive electrode powder B, composite positive electrode powder B and composite positive electrode powder C, and composite negative electrode powder D and composite negative electrode powder E is 2-5 μm.
[0016] As an embodiment of the present invention, the difference in particle size between the electrolyte powder and the composite positive electrode powder C, and between the electrolyte powder and the composite negative electrode powder D is 0-2 μm.
[0017] As an embodiment of the present invention, the positive electrode powder includes a positive electrode material, a sulfide electrolyte, a conductive agent, a thermoplastic material, and a binder.
[0018] As an embodiment of the present invention, the proportions of each component in the positive electrode powder are as follows by mass:
[0019] The composite positive electrode powder A comprises: 75-85 parts of positive electrode material, 10-20 parts of sulfide electrolyte, 1-3 parts of conductive agent, 0.8-1.2 parts of adhesive, and 2-4 parts of thermoplastic material;
[0020] The composite positive electrode powder B comprises: 45-55 parts of positive electrode material, 40-50 parts of sulfide electrolyte, 1-3 parts of conductive agent, 0.8-1.2 parts of adhesive, and 2-4 parts of thermoplastic material;
[0021] The composite positive electrode powder C comprises: 15-25 parts of positive electrode material, 70-80 parts of sulfide electrolyte, 1-3 parts of conductive agent, 0.8-1.2 parts of adhesive, and 2-4 parts of thermoplastic material.
[0022] As one embodiment of the present invention, the composite negative electrode includes a negative electrode material, silicon oxide, a sulfide electrolyte, a conductive agent, a binder and a thermoplastic material.
[0023] The composite negative electrode powder D comprises the following components in parts by mass: 25-35 parts of negative electrode material, 55-65 parts of sulfide electrolyte, 5-10 parts of silicon oxide, 1-3 parts of conductive agent, 0.8-1.2 parts of binder, and 1-3 parts of thermoplastic material;
[0024] The composite negative electrode powder E comprises the following components in parts by mass: 55-65% of negative electrode material, 10-20 parts of sulfide electrolyte, 15-25 parts of silicon oxide, 1-3 parts of conductive agent, 0.8-1.2 parts of adhesive, and 1-3 parts of thermoplastic material.
[0025] Preferably, the positive electrode material in the positive electrode powder includes one or more of a nickel-cobalt-manganese ternary positive electrode material, a lithium-rich manganese-based positive electrode material, and a lithium iron phosphate positive electrode material.
[0026] Preferably, the negative electrode material in the negative electrode powder is graphite.
[0027] Preferably, the sulfide electrolyte in the electrolyte powder, the positive electrode powder and the negative electrode powder includes one of LPSCl (argyrodite electrolyte) and LGPS (lithium germanium phosphorus sulfur electrolyte), and preferably they are the same electrolyte.
[0028] Preferably, the conductive agent in the positive electrode powder and the negative electrode powder is VGCF (nanocarbon fiber).
[0029] Preferably, the binder in the positive electrode powder and the negative electrode powder is one or more of PTFE (polytetrafluoroethylene) and PVDF (polyvinylidene fluoride). The binder is preferably 0.4-0.6 parts of PTFE and 0.4-0.6 parts of PVDF.
[0030] Preferably, the thermoplastic material in the positive electrode powder and the negative electrode powder includes one of polyamide, polyethylene, polypropylene, polyvinyl chloride, polystyrene and polyoxymethylene. The thermoplastic material is a low-viscosity thermoplastic agent, preferably polyamide (TPA), and its molecular structure is as follows:
[0031]
[0032] Thermoplastic materials can enhance the mechanical properties of solid electrolytes. Solid electrolytes are relatively brittle, and thermoplastic materials can serve as a flexible matrix to improve the flexibility and impact resistance of the electrolyte, preventing cracking during battery assembly or use. Secondly, it helps to improve the interfacial compatibility between the electrolyte and the electrode. It can make the solid electrolyte and electrode materials contact better, reduce the interface resistance, and improve the electrochemical properties of the battery, such as ion conductivity.
[0033] As an embodiment of the present invention, the thickness of the positive electrode powder layer is 75-90 μm, the thickness of the electrolyte powder layer is 45-60 μm, and the thickness of the negative electrode powder layer is 75-90 μm. Among them, the thickness of the composite positive electrode powder A layer is 25-30 μm, the thickness of the composite positive electrode powder B layer is 25-30 μm, and the thickness of the composite positive electrode powder C layer is 25-30 μm. The thickness of the composite negative electrode powder D layer is 37.5-45 μm, and the thickness of the composite negative electrode powder E layer is 37.5-45 μm.
[0034] The present invention also provides a method for preparing the all-solid-state battery cell, comprising the following steps:
[0035] S1. According to the structure of the layered powder battery, spray each powder layer in sequence to obtain a layered powder battery;
[0036] S2. Press the obtained layered powder battery cell to obtain an all-solid-state battery cell.
[0037] As an embodiment of the present invention, in step S1, the spraying method is electrostatic spraying. When spraying, it is preferred to spray the positive electrode powder layer first, then spray the electrolyte powder layer, and finally spray the negative electrode powder layer.
[0038] As an embodiment of the present invention, in step S2, the pressing method is warm isostatic pressing. The temperature of warm isostatic pressing is 120-180°C, the pressure is 100-300 MPa, preferably 130-200 MPa. The pressing direction is perpendicular to the direction of the powder layer.
[0039] The obtained all-solid-state battery cell includes a composite positive electrode layer, an electrolyte layer, and a composite negative electrode layer in sequence, wherein there is no obvious interface boundary layer between the composite positive electrode and the electrolyte, and between the electrolyte and the composite negative electrode, which can reduce the influence of the interface resistance on the battery cell.
[0040] The present invention also provides an application of an all-solid-state battery cell in the preparation of an all-solid-state battery. The application is specifically to weld and package the all-solid-state battery cell through tabs to obtain a finished all-solid-state battery with a three-dimensional staggered lithium ion conductive network.
[0041] The positive electrode powder of the present invention is electrostatically sprayed uniformly in the mold in the order of A, B, and C; then a layer of sulfide electrolyte is sprayed on the composite positive electrode layer; then the evenly mixed composite negative electrode powder is electrostatically sprayed uniformly on the surface of the electrolyte layer in the order of D and E; the powder is integrated and pressed by warm isostatic pressing to obtain a three-dimensional staggered lithium ion conductive network all-solid-state battery cell, which can be further used in an all-solid-state battery.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) The proportion of sulfide electrolyte in the composite positive electrode layers A, B, and C of the present invention gradually increases, while the proportion of sulfide electrolyte in the composite negative electrode layers D and E gradually decreases, so that lithium ions are staggered in the composite positive and negative electrode layers to form a three-dimensional staggered lithium ion conduction network, making the insertion / extraction of lithium ions more convenient and quick, thereby reducing the resistance of the battery.
[0044] (2) The present invention adopts the above technical scheme, and the composite positive electrode electrostatic powder spraying, electrolyte powder spraying and composite negative electrode powder spraying are configured step by step according to the above particle size and composition ratio. When the composite positive electrode layer, electrolyte layer and composite negative electrode layer are sprayed step by step, the electrolyte powder is better embedded with the composite negative electrode layer and the composite positive electrode layer to form a three-dimensional staggered lithium ion conduction network, thereby strengthening the combination of the two sides of the electrolyte layer with the composite positive electrode layer and the composite negative electrode layer respectively, and at the same time weakening the interface effect to reduce the interface impedance. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, which will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0046] Examples 1-3
[0047] A fully solid-state battery having a three-dimensional interlaced lithium ion conduction network is prepared, including an integrated spray-coated and pressed composite positive electrode layer, an electrolyte layer, and a composite negative electrode layer.
[0048] (1) The composite positive electrode layer consists of positive electrode powder and LPSCl, VGCF, TPA, PTFE, and PVDF.
[0049] The composite positive electrode is composed of three different particle sizes and corresponding ratios: A, B, and C. The particle size of the composite positive electrode A is Dmax≤15μm, the particle size of the composite positive electrode B is Dmax≤10μm, and the particle size of the composite positive electrode C is Dmax≤5μm.
[0050] The components of composite positive electrode A are as follows: positive electrode material accounts for 80%, LPSCl accounts for 14%, VGCF accounts for 2%, PTFE accounts for 0.5%, PVDF accounts for 0.5%, and TPA accounts for 3%;
[0051] The components of composite positive electrode B are as follows: positive electrode material accounts for 50%, LPSCl accounts for 44%, VGCF accounts for 2%, PTFE accounts for 0.5%, PVDF accounts for 0.5%, and TPA accounts for 3%;
[0052] The components of the composite positive electrode C are: positive electrode material accounts for 20%, LPSCl accounts for 74%, VGCF accounts for 2%, PTFE accounts for 0.5%, PVDF accounts for 0.5%, and TPA accounts for 3%.
[0053] (2) The electrolyte layer is composed of LPSCl with a particle size Dmax ≤ 5 μm.
[0054] (3) The composite negative electrode layer is composed of graphite, silicon oxide, LPSCl, PTFE, PVDF, and TPA;
[0055] The composite negative electrode is composed of two different particle sizes, D and E, and corresponding ratios. The particle size of the composite negative electrode D is Dmax≤5μm, and the particle size of the composite negative electrode E is Dmax≤10μm.
[0056] The components of the composite negative electrode D are graphite accounting for 30%, LPSCl accounting for 60%, silicon oxide accounting for 7%, PTFE accounting for 0.5%, PVDF accounting for 0.5%, and TPA accounting for 2%;
[0057] The components of the composite negative electrode E are graphite accounting for 62%, LPSCl accounting for 15%, silicon oxide accounting for 20%, PTFE accounting for 0.5%, PVDF accounting for 0.5%, and TPA accounting for 2%.
[0058] (4) The method for preparing the above-mentioned three-dimensional interlaced lithium ion conductive network all-solid-state battery cell comprises the following steps:
[0059] The uniformly mixed composite positive electrode powder is electrostatically sprayed uniformly in the mold in the order of A, B, and C (the total thickness of the positive electrode powder layer is 80 μm, and the thickness of each layer is the same); then a layer of sulfide electrolyte (thickness 50 μm) is sprayed on the composite positive electrode layer; then the uniformly mixed composite negative electrode powder is electrostatically sprayed uniformly on the surface of the electrolyte layer in the order of D and E (the total thickness of the negative electrode powder layer is 80 μm, and the thickness of each layer is the same); the powder is integrated and pressed by warm isostatic pressing (temperature of 150°C and pressure of 150 MPa) to obtain a three-dimensional staggered lithium ion conductive network all-solid-state battery cell;
[0060] (5) The above-mentioned battery cell is subjected to tab welding and aluminum-plastic film packaging to obtain a finished all-solid-state battery with a three-dimensional interlaced lithium ion conduction network.
[0061] The specific implementation is as follows:
[0062] Table 1 Specific parameters of Examples 1-3
[0063]
[0064] Embodiment 4-6
[0065] The difference between Example 4-6 and Example 1-3 is that the sulfide electrolyte is LGPS, and the temperature and pressure of the isostatic pressing treatment are 150° C. and 150 MPa.
[0066] The performance tests of the all-solid-state batteries with three-dimensional interlaced lithium ion conductive networks obtained in Examples 1-6 are shown in Table 2 below.
[0067] The tests of all-solid-state lithium batteries are as follows:
[0068] The all-solid-state lithium battery was placed under a constant temperature of 25°C, and constant current charging was performed at a current value of 0.1C (10h, calculated based on the mass of the positive electrode active material) relative to the theoretical capacity of the all-solid-state lithium battery, and the charging was terminated at a voltage of 4.3V. Then, the current was discharged at the same rate of 0.1C, and the discharge was terminated at a voltage of 2.5V. In this way, the coulombic efficiency and discharge capacity of the battery were obtained. Starting from the second cycle, 100 charge and discharge cycles were performed at 0.2C. After 300 weeks, the greater the discharge capacity retention rate, the better the cycle performance. Table 2 shows the cycle performance test of the three-dimensional interlaced lithium ion conductive network all-solid-state battery obtained in Examples 1-6.
[0069] Table 2 Performance of Examples 1-6
[0070]
[0071] Comparative Examples 1-6
[0072] The difference between Comparative Examples 1-6 and Examples 1-6 is that only an equal amount of composite positive electrode A is selected as the composite positive electrode, and only an equal amount of composite negative electrode E is selected as the composite negative electrode. The test results are shown in Table 3.
[0073] Table 3 Performance of Comparative Examples 1-6
[0074]
[0075] By comparing the test results of Examples 1-6 and the comparative examples, it can be seen that the all-solid-state battery with a three-dimensional interlaced lithium ion conduction network formed by the technical solution of the present invention has better performance than the battery compressed using a single-layer composite positive electrode A and a composite negative electrode E, which is beneficial to the internal lithium ion transmission and internal resistance reduction of the all-solid-state battery with a three-dimensional interlaced lithium ion conduction network of the present application.
[0076] Comparative Example 7
[0077] The difference between Comparative Example 7 and Example 1 is that the pressure of warm isostatic pressing is 150 MPa and the temperature is 25°C.
[0078] Comparative Example 8
[0079] The difference between Comparative Example 8 and Example 1 is that the pressure of warm isostatic pressing is 100 MPa and the temperature is 150°C.
[0080] The results of Comparative Examples 7-8 are shown in Table 4:
[0081] Table 4 Test results of comparative examples 7-8
[0082]
[0083] The results of Comparative Example 7 and Example 1 show that the isostatic pressing temperature has an important influence on the performance of the battery, and the performance of the battery without temperature treatment is worse than that of the battery with temperature treatment. This is because the application of temperature is conducive to TPA curing the battery structure, so that the positive and negative electrodes of the battery do not expand and rebound during the charge and discharge process.
[0084] From the results of Comparative Example 8 and Example 1, it can be seen that the performance of the battery cell treated with a small pressure is worse than that treated with a large pressure. This is because applying a large pressure is beneficial to compacting the battery cell structure so that the battery does not collapse during the charge and discharge process.
[0085] Comparative Example 9 (Comparison of unchanged particle size)
[0086] The difference between Comparative Example 9 and Example 1 is that the compositions of A, B and C remain unchanged and the particle sizes are all 5 μm.
[0087] Comparative Example 9 uses less positive electrode material and achieves the same effect as Comparative Example 1 by setting the gradient of the composition. Example 1 further sets the particle size gradient, and the effect is better.
[0088] Comparative Example 10 (Comparison of unchanged particle size)
[0089] The difference between Comparative Example 10 and Example 1 is that the composition of D and E remains unchanged, and the particle sizes of D and E are both 5 μm.
[0090] Comparative Example 11 (comparison with unchanged composition)
[0091] The difference between Comparative Example 11 and Example 1 is that the compositions of the composite positive electrodes A, B, and C are: 50% positive electrode material, 44% LPSCl, 2% VGCF, 0.5% PTFE, 0.5% PVDF, and 3% TPA; the compositions of the composite negative electrodes D and E are: 30% graphite, 60% LPSCl, 7% silicon oxide, 0.5% PTFE, 0.5% PVDF, and 2% TPA.
[0092] Comparative Example 12 (Comparison of Preparation Methods)
[0093] The difference between Comparative Example 12 and Example 1 is that the positive electrode powder, electrolyte powder and negative electrode powder are sprayed and pressed respectively to obtain a composite positive electrode layer, electrolyte layer and composite negative electrode layer respectively, and finally assembled to obtain a battery cell.
[0094] Table 5 Test results of comparative examples 9-12
[0095]
[0096] The results of Comparative Examples 9 and 10 and Example 1 show that the particle sizes of A, B, and C are all Dmax≤5μm, without a particle size distribution gradient, and their performance is poor. It can be seen that the three-dimensional staggered lithium ion conductive network with a particle size distribution gradient in the present invention improves the performance of the battery.
[0097] The results of Comparative Example 11 and Example 1 show that the particle sizes of D and E are both Dmax≤5μm, there is no particle size distribution gradient, and their performance is poor. It can be seen that the three-dimensional staggered lithium ion conductive network with a particle size distribution gradient in the present invention improves the performance of the battery.
[0098] From the results of Comparative Example 12 and Example 1, it can be seen that the finished battery cell obtained by pressing only the positive electrode, electrolyte, and negative electrode powder has poor performance. This is because no electrolyte, thermoplastic agent, and conductive agent are added to the positive and negative electrode materials, resulting in poor ion conduction and electronic conduction of the battery cell. The lack of thermoplastic agent causes powder shedding and structural collapse of the battery cell during the pressing process, resulting in poor performance.
[0099] The above specific embodiments are merely explanations of the present invention and are not limitations of the present invention. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, such modifications are protected by the patent law as long as they are within the scope of the claims of the present invention.
Claims
1. An all-solid-state battery cell having a three-dimensional interlaced lithium ion conductive network, characterized in that: The all-solid-state battery cell is a pressed layered powder cell; the layered powder cell comprises an electrolyte powder layer, and a positive electrode powder layer and a negative electrode powder layer respectively arranged on both sides of the electrolyte powder layer; The positive electrode powder layer includes a composite positive electrode powder C layer, a composite positive electrode powder B layer and a composite positive electrode powder A layer which are sequentially arranged on one side of the electrolyte powder layer from the inside to the outside; wherein the particle size of each component in the composite positive electrode powder A is 10 μm ≤ Dmax ≤ 15 μm, the particle size of each component in the composite positive electrode powder B is 5 μm ≤ Dmax ≤ 10 μm, and the particle size of each component in the composite positive electrode powder C is Dmax ≤ 5 μm; The negative electrode powder layer includes a composite negative electrode powder D layer and a composite negative electrode powder E layer which are sequentially arranged on the other side of the electrolyte powder layer from the inside to the outside; wherein the particle size of each component in the composite negative electrode powder D is Dmax≤5μm, and the particle size of each component in the composite negative electrode powder E is 5μm≤Dmax≤10μm; The particle size of the electrolyte powder is Dmax≤5μm; The particle size differences between composite positive electrode powder A and composite positive electrode powder B, composite positive electrode powder B and composite positive electrode powder C, and composite negative electrode powder D and composite negative electrode powder E are all 2-5 μm; The composite positive electrode powder layer A, the composite positive electrode powder layer B, and the composite positive electrode powder layer C all include sulfide electrolyte, and the proportion of sulfide electrolyte gradually increases. The composite negative electrode powder layer D and the composite negative electrode powder layer E all include sulfide electrolyte, and the proportion of sulfide electrolyte gradually decreases.
2. The all-solid-state battery cell according to claim 1, characterized in that: The particle size differences between the electrolyte powder and the composite positive electrode powder C, and between the electrolyte powder and the composite negative electrode powder D are all 0-2 μm.
3. The all-solid-state battery cell according to claim 1, characterized in that: The positive electrode powder includes a positive electrode material, a sulfide electrolyte, a conductive agent, a thermoplastic material, and a binder.
4. The all-solid-state battery cell according to claim 3, characterized in that: The proportions of each component in the positive electrode powder are as follows: The composite positive electrode powder A comprises: 75-85 parts of positive electrode material, 10-20 parts of sulfide electrolyte, 1-3 parts of conductive agent, 0.8-1.2 parts of adhesive, and 2-4 parts of thermoplastic material; The composite positive electrode powder B comprises: 45-55 parts of positive electrode material, 40-50 parts of sulfide electrolyte, 1-3 parts of conductive agent, 0.8-1.2 parts of adhesive, and 2-4 parts of thermoplastic material; The composite positive electrode powder C comprises: 15-25 parts of positive electrode material, 70-80 parts of sulfide electrolyte, 1-3 parts of conductive agent, 0.8-1.2 parts of adhesive, and 2-4 parts of thermoplastic material.
5. The all-solid-state battery cell according to claim 1, characterized in that: The negative electrode powder includes a negative electrode material, silicon oxide, a sulfide electrolyte, a conductive agent, a thermoplastic material, and a binder.
6. The all-solid-state battery cell according to claim 5, characterized in that: The proportions of each component in the negative electrode powder are as follows: The composite negative electrode powder D includes the following components in parts by mass: 25-35 parts of negative electrode material, 55-65 parts of sulfide electrolyte, 5-10 parts of silicon oxide, 1-3 parts of conductive agent, 0.8-1.2 parts of binder, and 1-3 parts of thermoplastic material; The composite negative electrode powder E comprises the following components in parts by mass: 55-65 parts of negative electrode material, 10-20 parts of sulfide electrolyte, 15-25 parts of silicon oxide, 1-3 parts of conductive agent, 0.8-1.2 parts of adhesive, and 1-3 parts of thermoplastic material.
7. The all-solid-state battery cell according to claim 1, characterized in that: The positive electrode material in the positive electrode powder includes one or more of a nickel-cobalt-manganese ternary positive electrode material, a lithium-rich manganese-based positive electrode material, and a lithium iron phosphate positive electrode material; and / or, the negative electrode material in the negative electrode powder is graphite; And / or, the sulfide electrolyte in the electrolyte powder, the positive electrode powder, and the negative electrode powder includes one of LPSCl and LGPS; And / or, the conductive agent in the positive electrode powder and the negative electrode powder is VGCF; And / or, the binder in the positive electrode powder and the negative electrode powder is one or more of PTFE and PVDF; And / or, the thermoplastic material in the positive electrode powder and the negative electrode powder includes one of polyamide, polyethylene, polypropylene, polyvinyl chloride, polystyrene and polyoxymethylene.
8. The all-solid-state battery cell according to claim 1, characterized in that: The thickness of the positive electrode powder layer is 75-90 μm, the thickness of the electrolyte powder layer is 45-60 μm; the thickness of the negative electrode powder layer is 75-90 μm; And / or, the thickness of the composite positive electrode powder A layer is 25-30 μm, the thickness of the composite positive electrode powder B layer is 25-30 μm, and the thickness of the composite positive electrode powder C layer is 25-30 μm; And / or, the thickness of the composite negative electrode powder D layer is 37.5-45 μm, and the thickness of the composite negative electrode powder E layer is 37.5-45 μm.
9. A method for preparing an all-solid-state battery cell as claimed in claim 1, characterized in that: The steps include: S1. According to the structure of the layered powder battery, spray each powder layer in sequence to obtain a layered powder battery; S2. Press the obtained layered powder battery cell to obtain an all-solid-state battery cell.
10. Use of the all-solid-state battery cell as claimed in claim 1 in the preparation of an all-solid-state battery.
Citation Information
Patent Citations
Low-internal-resistance solid sulfide electrolyte lithium battery cell, battery and preparation method thereof
CN111313101A
Multi-layer all-solid-state battery and preparation method and application thereof
CN117996218A